2020
DOI: 10.23939/chcht14.03.372
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Activity and Phytochemical Screening of the Apricot Cake Extract: Experimental and Theoretical Studies

Abstract: The aim of this study was to determine the chemical composition and antioxidant potential of the apricot pomace extract (АСЕ). The apricot pomace was extracted using ethanol (EtOH), silicone (D5) and a mixture of silicone and ethanol. The chemical constituents were analyzed by gas chromatography-mass spectrometry (GC-MS). The antioxidant capacity was evaluated using a variety of antioxidant assays (total antioxidant activity, reducing power and catalase activity). Quantum chemical descriptors such as the front… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…6a) except the presence of strong signal around 988 cm −1 which could be attributable to the bending vibration of C-H lactic acid. Phenolic compounds are considered as a major group of compounds that contribute to the antioxidant activity of by-products of fruit and vegetables [52]. To better understand the relationship between the antioxidant activity and total phenolic content (TPC) and total flavonoid content (TFC), the TPC and TFC of the sample extracts were determined.…”
Section: Resultsmentioning
confidence: 99%
“…6a) except the presence of strong signal around 988 cm −1 which could be attributable to the bending vibration of C-H lactic acid. Phenolic compounds are considered as a major group of compounds that contribute to the antioxidant activity of by-products of fruit and vegetables [52]. To better understand the relationship between the antioxidant activity and total phenolic content (TPC) and total flavonoid content (TFC), the TPC and TFC of the sample extracts were determined.…”
Section: Resultsmentioning
confidence: 99%
“…Since the electrophilicity index ( w ) characterizes the capacity of a system to gain an electron is an additive parameter to predict the chemical reactivity of a compound, it gives an indication on the deterioration of the binding energy due to a maximum electron flow between a donor and an acceptor. 29 Thus, in terms of electrophilicity index (w), the most reactive antioxidant compound is confirmed to be EGCG (0.4964 eV), whereas the lowest value (0.3717 eV) matched with EC.…”
Section: Computation Of Total (Average) Antioxidant Capacitymentioning
confidence: 87%
“…Recent studies have demonstrated the correlation between energy of HOMO (E HOMO ) and the free radical scavenging activity. 29 Molecules with lower HOMO energy are less likely to donate electrons. The elect-ronic density distribution of HOMO enables the prediction of the most probable sites responsible for electron transfer and free radical attack.…”
Section: Computation Of Total (Average) Antioxidant Capacitymentioning
confidence: 99%
See 1 more Smart Citation
“…The major phytochemical groups which impart biological activities against infections are alkaloids, phenols, polyphenols, quinones, flavonoids, tannins, terpenes, polypeptides, essential oil, and other compounds. 5,6 The basilic "Ocimum basilicum L." is a plant of the Lamiaceae family. This annual aromatic herb native to India, and widely cultivated in Algeria hardly exists in the wild, is morphologically very variable, perennial in a tropical climate and generally known under the name "Lahbeq" "Hamahim" and also "Hebeqelailaa".…”
Section: Introductionmentioning
confidence: 99%